2020
DOI: 10.1177/1464420720942554
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and microstructural analysis of Al-Al2O3/B4C hybrid composites

Abstract: The present work aims to enhance the mechanical performance of monolithic Al alloy and single reinforced metal matrix composite using a hybridization technique. The microparticles of alumina and boron carbide were reinforced into cast Al alloy (6061) in a systematic varying ratio (i.e.100/0, 75/25, 50/50, 25/75 and 0/100) to prepare the hybrid metal matrix composites via stir casting method. The mechanical properties (i.e. tensile, impact, hardness and flexural) of the prepared composites were investigated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This improvement in hardness is a result of the addition of hard ceramic particles, lower porosity, and uniform dispersion of reinforcements in the matrix. 26 The addition of reinforcement particles causes the refinement in grains, and thermal mismatch among reinforcement and matrix interfaces influences the hardness of the hybrid composites in addition to Hall-Petch and Orowan strengthening mechanism. 27 During indentation, hard ceramic particles cause resistance to plastic deformation, thereby shifting the load from a soft and ductile matrix to hard reinforcements (LBA and B 4 C).…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…This improvement in hardness is a result of the addition of hard ceramic particles, lower porosity, and uniform dispersion of reinforcements in the matrix. 26 The addition of reinforcement particles causes the refinement in grains, and thermal mismatch among reinforcement and matrix interfaces influences the hardness of the hybrid composites in addition to Hall-Petch and Orowan strengthening mechanism. 27 During indentation, hard ceramic particles cause resistance to plastic deformation, thereby shifting the load from a soft and ductile matrix to hard reinforcements (LBA and B 4 C).…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…However, despite their numerous advantages, conventional MMCs often exhibit certain limitations, such as limited fracture toughness, insufficient thermal conductivity, and a high coefficient of thermal expansion. To address these limitations and further optimize the properties, the concept of Hybrid Metal Matrix Composites (HMMCs) emerged [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the surface composite exhibited higher hardness and ballistic e ciency due to the dispersion strengthening mechanism induced by the reinforced particles. Gupta and Gupta [21] prepared Al-B 4 C/Al 2 O 3 hybrid composite using the stir casting route and reported enhanced mechanical properties and reduced porosity as compared to Al matrix and single reinforced metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%